The role of extracellular vesicles in vascular calcification in chronic kidney disease - Zhao, Huan; Liu, Haojie; Liu, Yueming; Jin, Juan; He, Qiang; Lin, Bo (Frontiers in Medicine, 2022)
Widespread vascular calcification (VC) in patients with chronic kidney disease (CKD) is the pathological basis for the development of cardiovascular disease, and VC has been identified as an independent risk factor for increased cardiovascular mortality in cases of CKD. While VC was earlier thought to be a passive deposition process following calcium and phosphorus supersaturation, recent studies have suggested that it is an active, modifiable, biological process similar to bone development. The involvement of extracellular vesicles (EVs) in the process of VC has been reported as an important transporter of material transport and intercellular communication. This paper reviews the mechanism of the role of EVs, especially exosomes, in VC and the regulation of VC by stem cell-derived EVs, and discusses the possible and promising application of related therapeutic targets in the clinical setting.